2022
DOI: 10.1007/s42000-022-00389-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diet and treadmill running on the hypothalamic Kiss-1–GPR54 signaling pathway in male growing rats

Abstract: Background Kiss-1 neuron, one of the metabolic sensors in the hypothalamus, is necessary for puberty initiation. It acts through G protein-coupled receptor, known as GPR54. In this study, the mechanism of the hypothalamic Kiss-1–GPR54 signaling pathway in a high-fat diet and exercise was investigated in growing male rats. Methods A total of 135 3-week-old male weaned rats were kept on a high-fat diet (HFD) and exercise (60–70% $$\dot{\mathrm V}{\mathrm O}_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the ovary of rat offspring, the comparison of Kisspeptin and GnRHR does not exhibit persistent changes after perinatal exposure to CPF, HFD, and coex, whereas several studies have shown a negative link between pesticide exposure and Kisspeptin expression [ 30 , 36 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the ovary of rat offspring, the comparison of Kisspeptin and GnRHR does not exhibit persistent changes after perinatal exposure to CPF, HFD, and coex, whereas several studies have shown a negative link between pesticide exposure and Kisspeptin expression [ 30 , 36 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%